Subgaleal haemorrhage in the newborn: A call for early diagnosis and aggressive management. (11th August 2014) - Colditz, Michael J; Lai, Melissa M; Cartwright, David W; Colditz, Paul B
Abstract Subgaleal haemorrhage (SGH) is an important cause of preventable morbidity and mortality in the neonate. Its increased prevalence in recent years has coincided with the rise in the number of births assisted by vacuum extraction. Three deaths in Australia within the last 7 years have been the subject of two coronial inquests. Subsequent coronial reports have highlighted that neonatal death from SGH can be prevented if appropriate attention is paid to identification of risk factors, early diagnosis, close observation and aggressive treatment. To prevent unnecessary deaths, all involved in the care of the baby after birth need to be aware of the importance of prompt diagnosis, monitoring and early treatment of SGH.